Nilai-Nilai Sufistik Ashab al-Qahwah di Kancakona Kopi Sumenep - Moh Ali Rizqon MD; M. Mushthafa (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to describe and identify coffee practice activities at the Kancakona Kopi shop, Sumenep Regency. Where this practice has a strong relationship to the elements or values of Sufism. This research is qualitative research using a phenomenological approach. The research data sources are the Kancakona Kopi shop manager, consumers, and figures or the public who are directly involved in the practice of drinking coffee, especially in the activities offered at the shop. The results of this research show that the practice of drinking coffee in the shop is; drinking coffee while reciting the Koran, drinking coffee while sharing, and drinking coffee while staying in touch with alumni or the community are coffee practices that are in harmony with Sufistic nuances. So in the end the value of feeling calm (ithmi'nanu al-qalbi), calm with the medium of friendship, and gratitude for actions became something that was very widespread in Ashab al-Qahwah in the shop.